IDENTIFIKASI KAWASAN PENGEMBANGAN JERUK DAN RESPONS PETANI TERHADAP PENUMBUHAN KOPERASI DI KABUPATEN REJANG LEBONG BENGKULU - Ishak, Andi; Fauzi, Emlan; Ramon, Erpan; Astuti, Herlena Bidi; Musaddad, Darkam (Jurnal AGRISEP, 2020)
Farmer cooperatives are legal entities whose existence is very important to increase the bargaining position of farmers in the agribusiness system on an agricultural commodity development area. This study aims to identify the citrus development area and analyze farmers' responses to cooperative formation in citrus development area in Rejang Lebong Regency. The study was conducted from February to April 2019 with primary data collection through interviews and surveys and supported by secondary data. Interviews were conducted to identify areas of citrus development. While the data collected in the survey are farmer characteristics (age, formal education, non-formal education, number of family dependents, area of garden ownership) and farmers’ responses to cooperative. The farmers’ response variable is a response to the cooperatives formation, cooperative forms, cooperative membership, service time, and cooperative management, which are measured using a Likert scale. Data analysis was carried out descriptively and inferentially using Spearman Rank correlation. This study concluded that the citrus development area in Rejang Lebong Regecy was in accordance with the Decree of the Rejang Lebong Regent Number 180.60. II Year 2018 which meets the requirements of Minister of Agriculture Regulation 18/2018 is only in Pal 7 Village, Bermani Ulu Raya Subdistrict. The citrus farmer’s response to the cooperative formation is positive. The response was significantly positively related to the area of garden ownership.